A Comparisson of Synchronous and Nonsynchronous Boost Converter - Mohamad Isnaeni Romadhon; Trias Andromeda; Mochammad Facta; Agung Warsito (IAES Indonesia Section, 2016)
Modern electronic systems require resources with high efficiency. The efficiency of direct current to dicrect current converters as a power source can be increased by replacing a diode with MOSFET. The use of MOSFET is expected to reduce power loss as the internal resistance of MOSFET is lower than a diode. To implement the propossed idea, a boost type direct current chopper and TL494 as PWM generator circuit were applied in this work. MOSFET is used in synchronization mode to replace diode at conventional topology of chopper.. The proposed circuit and conventional topology were made and their performance were observed. The efficiency of both circuit were compared and analyzed. The result of the experiments showed that the efficiency of converter within MOSFET at synchronization mode is proportional with the increment of duty cycle, while at conventional topology the efficiency remain stable at any duty cycle. Synchronous boost converter is more efficient than nonsynchronous boost converter at duty cycle over than 40%.